Documentary Sources and Archives Ladies Residence in Madrid (1926-1936) - Codina-Canet, María Adelina; San Segundo, Rosa (Revista General de Información y Documentación, 2015)
An aproppiate date to question the archival documentary sources to the “Residencia de Señoritas de Madrid” research, is 2015, in order to it’s the centenary of its creation. The work concerned describes the archive’s documentation and details the documentary collection from own archive of the institution, which marked a milestone in the educational activity and the access to higher education for spanish women. The documentary collection is digitized and provides query tools to the database to retrieve information about activities and services supplied by “Residencia”. The fund is located in 100 boxes, and there are estimated 30.000 documents. The documentary series “Correspondencia” contains more than 13.000 documents. This is the series which more contains. The study examines this documentary series because of its importance and projection at Gender Studies and Women’s History. It’s essential to know a lot of this documents, in order to know information about the institution managment and the relationship between influential people in intellectual areas and politicians of that time with the Institution or its director. Finally, this work describes the diposited documentation in others archives that can be interesting for following researchs.